2012
DOI: 10.1007/s00109-012-0932-x
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 inhibits expression of PUMA in gastric cancer cells

Abstract: During cancer development, tumor suppressor genes were silenced by promoter methylation or histone deacetylation. Histone deacetylases (HDACs) are important to maintain histone deacetylation. HDAC inhibitors (HDACis) were thus proposed as a new therapeutic approach to cancer. The current study aims to understand the effect and molecular mechanisms of HDACis on gastric cancer cells. Trichostatin A (TSA) significantly inhibited the growth of gastric cancer cells by inducing apoptosis. Gene profiling results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Inhibition of HDAC8 by methylselenopyruvate (MSP), a competitive inhibitor of HDAC8, was sufficient to activate BMF transcription and promote BMF-mediated apoptosis in colon cancer cells (Kang et al 2014). HDAC3 downregulates PUMA expression in gastric cancer cells and HDACi, like TSA, promotes PUMA expression through enhancing the binding of p53 to the PUMA promoter (Feng et al 2013). TSA treatment can also effectively overcome resistance to DNA damage–induced cell death by reactivating PUMA expression in renal cell carcinoma cells (Zhou et al 2014).…”
Section: Possible Mechanisms Of Hdacs In Cancer Developmentmentioning
confidence: 99%
“…Inhibition of HDAC8 by methylselenopyruvate (MSP), a competitive inhibitor of HDAC8, was sufficient to activate BMF transcription and promote BMF-mediated apoptosis in colon cancer cells (Kang et al 2014). HDAC3 downregulates PUMA expression in gastric cancer cells and HDACi, like TSA, promotes PUMA expression through enhancing the binding of p53 to the PUMA promoter (Feng et al 2013). TSA treatment can also effectively overcome resistance to DNA damage–induced cell death by reactivating PUMA expression in renal cell carcinoma cells (Zhou et al 2014).…”
Section: Possible Mechanisms Of Hdacs In Cancer Developmentmentioning
confidence: 99%
“…However, following HDAC inhibition, acetylation of p53 has been reported in several tumor systems, which has been related to p53 stabilization, cell cycle arrest, and apoptosis [132-134]. More recently, studies have shown that HDAC inhibitor TSA prompts PUMA expression to induce apoptosis in gastric cancer cells via two independent ways: p53 stabilization and p53 interaction with the PUMA promoter through the inhibition of HDAC3 [135]. …”
Section: Signaling Pathways Involved In Hdaci-induced Apoptosismentioning
confidence: 99%
“…45 Briefly, cells were first fixed with 4% formaldehyde. Cells were then lysed and chromatin was harvested and fragmented using enzyme digestion.…”
Section: Chromatin Immunoprecipitationmentioning
confidence: 99%